Extracorporeal Photopheresis (ECP) and the Potential of Novel Biomarkers in Optimizing Management of Acute and Chronic Graft vs. Host Disease (GvHD) - Mankarious, Matthew; Matthews, Nick C.; Snowden, John A.; Alfred, Arun (Frontiers in Immunology, 2020)
As the use of haematopoietic stem cell transplantation (HSCT) has become a more widespread and effective treatment for haematological malignant and non-malignant conditions, the need to minimise the harmful effects of graft-versus-host disease (GvHD) has become more important in achieving good outcomes. With diagnosis of GvHD reliant on its clinical manifestation, research into biomarkers for the diagnosis, progression, and even for the prediction of disease, is imperative to combating the high levels of morbidity and mortality post-HSCT. Despite the development of novel treatment approaches to GvHD, corticosteroids remain the standard first-line treatment, with immunosuppressant therapies as second-line options. These strategies however have significant limitations and associated complications. Extracorporeal Photopheresis (ECP) has shown to be effective and safe in treating patients with symptomatic GvHD. ECP has been shown to have varied effects on multiple parts of the immune system and does not appear to increase the risk of relapse or infection in the post HSCT setting. Even so, ECP is logistically more complex to organise and requires patients to be sufficiently stable. This review aims to summarise the potential role of biomarkers to help guide individualised treatment decisions in patients with acute and chronic GvHD. In relation to ECP, robust biomarkers of GvHD will be highly useful in informing patient selection, intensity and duration of the ECP schedule, monitoring of response and other treatment decisions alongside the concurrent administration of other GvHD therapies. Further research is warranted to establish how GvHD biomarkers are best incorporated into ECP treatment pathways with the goal of tailoring ECP to the needs of individual patients and maximising benefit.